Impact of COVID-19 Pandemic on Patients With Neurodegenerative Diseases - Hu, Chao; Chen, Cao; Dong, Xiao-Ping (Frontiers in Aging Neuroscience, 2021)
COVID-19 pandemic has already produced great impacts on global health security and social-economy. Elderly, particularly those with underlying diseases, are suffering from higher fatality rate. Neurodegenerative diseases are a group of incurable neurological disorders of loss of neuron and/or myelin sheath, which affect hundreds of millions of elderly populations and usually need long-term care. Older population is one of the most vulnerable to COVID-19 pandemic. In this report, we reviewed the current status of COVID-19 on the patients with several neurodegenerative diseases, particularly Alzheimer’s disease, Parkinson’s disease, prion disease, and amyotrophic lateral sclerosis. Meanwhile, the potential mechanisms of SARS-CoV-2 infection in the pathogenesis of neurodegenerative diseases were also summarized.